Updates in Chimeric Antigen Receptor T-Cell (CAR-T) Therapy for Lymphoma and Leukemia from the Annual Meeting of American Society of Hematology 2019. (August 2020) - Bukhari, Ali; Siglin, Jonathan; Lutfi, Forat; Kansagra, Ankit J.; Yared, Jean; Rapoport, Aaron P.; Dahiya, Saurabh
Abstract: Chimeric Antigen Receptor T-cell (CAR-T) therapy has revolutionized the field of hematologic malignancies and are potentially curative in patients with previously limited options. This review highlights key abstracts focusing on clinical studies in CAR-T therapy in leukemia and lymphoma presented at the 61 st annual meeting of the American Society of Hematology (December 2019, Orlando, FL). Selected studies discuss data on novel CAR-T constructs aimed at enhancing efficacy and durability of responses, improving toxicity mitigation strategies, challenging clinical scenarios in routine clinical practice for standard of care CAR-T therapy (role of bridging therapy, CNS involvement, and quality of life studies), and new technologies aiming to decrease production time to minimize delay in definitive therapy, all within the rapidly-evolving cellular immunotherapy landscape.